Comparative Ex Vivo Evaluation of Two Electronic Percussive Testing Devices Measuring the Stability of Dental Implants. Issue 12 (1st December 2014) - Geckili, Onur; Bilhan, Hakan; Cilingir, Altug; Bilmenoglu, Caglar; Ates, Gokcen; Urgun, Aliye Ceren; Bural, Canan
Abstract : Background: A comparative ex vivo study was performed to determine electronic percussive test values (PTVs) measured by cabled and wireless electronic percussive testing (EPT) devices and to evaluate the intra‐ and interobserver reliability of the wireless EPT device. Methods: Forty implants were inserted into the vertebrae and forty into the pelvis of a steer, a safe distance apart. The implants were all 4.3 mm wide and 13 mm long, from the same manufacturer. PTV of each implant was measured by four different examiners, using both EPT devices, and compared. Additionally, the intra‐ and interobserver reliability of the wireless EPT device was evaluated. Results: Statistically significant differences ( P <0.05) were observed between PTVs made by the two EPT devices. PTVs measured by the wireless EPT device were significantly higher than the cabled EPT device ( P <0.05), indicating lower implant stability. The intraobserver reliability of the wireless EPT device was evaluated as excellent for the measurements in type II bone and good‐to‐excellent in type IV bone; interobserver reliability was evaluated as fair‐to‐good in both bone types. Conclusion: The wireless EPT device gives PTVs higher than the cabled EPT device, indicating lower implant stability, and its inter‐ and intraobserver reliability is good and acceptable.